Inovasi Patty Bites Crispy dengan Proporsi Patin:Puree Ubi dan Penambahan Brokoli dengan Karakteristik Sensori - Alexander, Rendy Jhonatan; Any Sutiadiningsih; Sri Handajani; Ila H.P. Dewi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Patty Bites Crispy is a nutritious snack made from catfish, white sweet potato, and broccoli. This study was experimental in nature. Data were collected through observation involving five trained panelists and thirty semi-trained panelists using a scoring scale instrument (5–1). The data were analyzed using multiple Analysis of Variance (ANOVA). The results showed that the best formulation was 85% catfish, 15% white sweet potato, and 20% broccoli in terms of sensory characteristics. This combination produced the best attributes, including a pale cream color with green fibers, uniform bite-sized shapes, a crispy exterior with a soft interior, a distinctive aroma, and a balanced flavor. The nutritional content per 100 grams of product includes 54.05% carbohydrates, 13.65% protein, 6.05% fat, and 98 mg/100g beta-carotene. Recommendations for further research include: (1) conducting shelf-life analysis through moisture content, water activity (aw), and sensory observation during storage; (2) performing microbiological testing to ensure product safety during medium to long-term storage; and (3) carrying out production cost analysis and price estimation to assess market feasibility.